THE TEACHING OF COST ACCOUNTING. - Newlove, G. H. (The Accounting Review, 1931)
Abstract The article presents an interview with the author on the teaching of cost accounting. The article also presents comments of scholar Gould L. Harris on answers given by the author. In response to a query about the future use of cost accounting by students, the author replied that during the last ten year I have made a practice of asking my cost accounting students whether or not they expected to work in a factory after graduating. Less than five percent replied in the affirmative. This percentage is all the more important because most of my students have been residents of Washington and Baltimore. Therefore, it can be stated that the main purpose of the Cost Accounting course is not to directly prepare students for future work in factories. Indirect uses students will make of cost accounting seem to be chief reasons for giving the course. All students will use ideas that are given of, accounting controls, systems of internal check, computing costs according to suitable bases, departmentalization of expenses, detailed interlocking of paper work, adaptation of paper work and accounting routine to meet local company's condition, preparation and use of budgets, use of budgetary reserves and preparation and use of accounting reports.